Pemberdayaan Ibu Rumah Tangga Melalui Pelatihan Pembuatan Nugget Kupang di Desa Karang Gading - Siti Zubaidah; Ibnu Hajar (Jendela PLS: Jurnal Cendekiawan Ilmiah Pendidikan Luar Sekolah, 2021)
The problems in this study are the number of housewives who have free time and still have a fairly low income level and the lack of knowledge and skills of housewives in processing seafood without realizing that this potential can be a business opportunity that can increase family income. The purpose of this study was to describe the process of empowering housewives through making kupang nuggets in Karang Gading village. The empowerment theory used is Mustafa Kamil (2007). Training is a process of empowerment and learning carried out by individuals (community members) in learning something in order to improve abilities, skills, and behavior in work and daily life in supporting their economy (income). This theory explains that empowerment is a process of providing knowledge and skills to the community with the aim of improving the quality of life which is expected if these skills are realized will increase family income. This research is a descriptive study using a qualitative approach. Data collection tools used are observation sheets, interviews and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results and discussion of the research explained that the training process for making kupang nuggets was divided into three stages, namely the planning, implementation and evaluation stages. Materials on packaging and marketing of kupang nuggets were also delivered in the training. Keywords: Empowerment; Kupang Nugget Making Training